Questioning personal tutoring in higher education: an activity theoretical action research study. Issue 1 (1st January 2021) - Stuart, Kaz; Willocks, Katie; Browning, Ruth
ABSTRACT: Personal tutoring as an academic role is neither innovative nor one-dimensional. Engagement in the personal tutoring system correlates to student retention and ultimately achievement. Today the role is considered extensive with the Personal Tutor endeavouring to provide students with both academic and personal support. Whilst literature recognises the value of personal tutoring, little is known of role perceptions or associated practice. The study, undertaken with staff across two University of Cumbria departments, took an action research approach and utilised semi-structured interviews to explore their personal tutoring role perceptions and practice. Analysis was abductive, first through inductive open coding thematic analysis, then deductive, considering the categories and themes using Activity Theory. Key themes, contradictions and areas of development recommended for practice and policy are considered.